Pengentasan Buta Aksara melalui Program Keaksaraan Dasar di Desa Selebung Ketangga Lombok Timur - Wibawa, Indah Safitri; Sumardi, Lalu; Kurniawansyah, Edy (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Basic Literacy Education (KD) is an important program to resolve the problem of illiteracy in Selebung Ketangga Village. The KD program is one of the educational services outside of school to develop community members' reading, writing and arithmetic skills in Indonesian. Therefore, it is important to know the motivation and benefits of the KD program for society. This research uses a descriptive qualitative approach. Through observation, interviews and documentation. The researcher looked at how the illiteracy eradication program was in Selebung Ketangga Village. Data collection was carried out using purposive sampling, namely the researcher interviewed research informants. The observation results show that in the process of mastering basic understanding the participants routinely participate in learning activities for three hours from 14:00-16:00 and every day the participants have learning goals that must be achieved. Meanwhile, during the activity which lasted for several days, participants had different memory abilities, such as participants' memory which was very low and there were also some participants who had quite good memory, this was due to the age of the participants and the inhibiting factors found by The researcher said that some participants were unable to take part in learning activities because they were busy with other things, namely work. Based on the results of interviews and document analysis, it is known that there is a development of abilities that take part in KD activities, especially in daily activities and active participation in learning activities.